Dextromethorphan Role on Cough Suppression and Patient Procedure Tolerance in Flexible Bronchoscopy - Aqil, Mehvish; Imran, Mehr Muhammad; Usman, Umar; Musharaf, Saqib; Ahmed, Zaheer; Hamad, Ali (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the role of Dextromethorphan on cough suppression and patient procedure tolerance in flexible bronchoscopy.Study Design: Quasi-experimental study.Place and Duration of Study: Pulmonology Department, District Head Quarters Hospital, Faisalabad Pakistan, from Oct 2019 to Mar 2020.Methodology: Patients were divided into Group-1 and Group-2. Group-1 was given syrup Dextromethorphan 20miligram one hour before bronchoscopy and Group- 2 was given a placebo one hour before procedure. During procedure, oxygen saturation and blood pressure were recorded continuously by monitor. 10cm Visual analogue scale was used to chart their cough perception where 0 taken as no cough and 10 as incessant cough. Patients recorded their tolerability of procedure after 2 hours on 10cm visual analogue scale.Results: Mean age of whole study population, Group-A and Group-B was 48.80+11.24, 46.63+11.70 and 47.72+11.43 respectively. Females were 25(41.7%) and males were 35(58.3%). Both groups have same mean SpO2 with supplemental oxygen. Four patients had an oxygen saturation below 90% during flexible bronchoscopy in both groups (p-value 0.647). Similar doses of Midazolam were used in the Dextromethorphan and placebo groups (p-value 0.879). The perception of cough by the patient, assistant staff and bronchoscopist in Dextromethorphan group 1 was significantly low (p-value 0.041, 0.0001, 0.037 respectively). Duration of procedure was also significantly lower in Dextromethorphan group p-value 0.0001.Conclusion: Dextromethorphan use in addition to Midazolam and local anesthetic during flexible bronchoscopy results in